WATER EXTRACT OF SWEET POTATO LEAF IMPROVED LIPID PROFILE AND BLOOD SOD CONTENT OF RATS WITH HIGH CHOLESTEROL DIET - Sumardika, I Wayan; Jawi, I Made (Medicina; Vol 43 No 2 (2012): Mei 2012, 2013)
Food stuffs with high flavonoids content  are believed to prevent various diseases caused by oxidative stress because of its antioxidants effect.  Purple sweet potato leaves have been proved containing high flavonoids, and can be developed very easily. To prove antioxidant and hypolipidemic properties of the water extract of purple sweet potato leaves, one research was conducted in the Department of Pharmacology, Faculty of Medicine, Udayana University. The study design was randomized control group pre- and post-test.  Twenty adult male wistar rats were divided into two groups of 10 rats. Both groups of rats were given high-cholesterol diet for three months to induce dyslipidemia. Control group of 10 rats were given only high-cholesterol diet alone, whereas the treatment group also treated with purple sweet potato leaf water extract with a dose of 6 cc per day divided into two doses. Before treatment and after treatment, lipid profile and blood SOD levels were measured. The results showed a decrease in total cholesterol, triglycerides and LDL cholesterol significantly in the treated group ( P = 0.0001). In the treatment group there was also an increase in HDL cholesterol and blood SOD which was significantly differ than the control group ( P = 0.0001). From the results of this study, it can be concluded that administration of water extract of purple sweet potato leaves can improve the lipid profile and increase blood SOD of rat given high-cholesterol diet.
Keywords: sweet purple potato leaf, lipid profile, high-cholesterol foods, rat